ANALISA KEGAGALAN SWING DRIVE WHEEL EXAVATOR M 322 C DAN USAHA PENCEGAHANNYA - Andika Syofyan (Jurnal Teknik Industri Terintegrasi, 2018)
There has been a breakdown and failure of Swing Drive Wheel Exavator M 322 C is not yet known the exact cause, it is necessary to study scientific and laboratory testing for the event can be clearly known cause, by identifying, inventegasi include systems and procedures for the operation, maintenance, testing laboratory on style and material (macrostruktur, microstruktur), based on data analysis of the causes of damage and failure can be revealed.Visually test shows that the defective object is pinion gear suffered damage types: surface damage (wear / wear and deformation). Furthermore, through testing fraktografi, metallographic, hardness, chemical composition and SEM, then we can determine the factors causing damage to the pinion gear, whether because of metallurgy (material and / or manufacturing), or because of assembly / installation, the factors of operation, or because maintenance factor. The results obtained from these tests can provide recommendations and suggestions were appropriate and safe in the use of materials as well as efforts to prevent damage to the more fatal the following steps - steps appropriate care to anticipate failure event at the Pinion Gear Swing Drive Wheel Exavator M 322 C in particular ,Main cause of failure (wear and tear) on the pinion gear is the fault of operations conducted by the operator, that there has been a shock loads when the operator operate exavator when conducting swing. Shock loads occur due to collisions between the bucket with rocky ground. The incident repeated - again occur so slewing ring bearing experience rocking. Wear and tear experienced by pinion gear starts from wear adhesive (adhesive wear) followed by abrasive wear (abrasive wear). Changes in the condition of wear and tear will cause phase transformation of the material that rotates and rub against each other, it is this which causes the pinion gear wear out.